The beginner's guide to growing great vegetables - Forkner, Lorene Edwards (Timber Press, 2021)
"Expert gardener Lorene Edwards Forkner shares all the information you need to create a thriving garden, from facts about soil and sun to tips on fertilizing, mulching, and watering. Regional planting charts show what to plant when, and a month-by-month planner takes you from January through December... Whether your garden grows in the ground, on a balcony, or in containers on a sunny patio, this is your guide to grow-your-own success."--Page 4 of cover.